PUBLICATION OF SCIENTIFIC PERIODICALS AT UNIVERSITIES:NEW CHALLENGES, PARTICIPANTS, TECHNOLOGY - Kolesnykova, T. O.; Kliushnyk, I. A. (Science and Transport Progress, 2015)
Purpose. Publication of scientific periodicals in the Universities is very important and necessary element in the infrastructure of scientific communication. The aim of the article is: 1) providing a new model of publication system of the University scientific periodicals (on the example of Dnipropetrovsk National University of Railway Transport named after Academician V. Lazaryan – DNURT); 2) studying the peculiarities of the «Library publishing» model (Library Publishing) and library as a new participant in the publication of world scientific periodicals of the University; 3) description of the developed software automation typesetting of scientific articles and their integration into international databases of scientific and technical information. Methodology. The scientists investigated: 1) the system of publication of scientific periodicals at DNURT; 2) integration system of electronic versions of periodicals and individual articles of scientists from DNURT into the world scientific databases; 3) publishing activity of the scientific and technical library of the University. Findings. The authors proved the need for the fast updates in each higher education institution of Ukrainian management system of scientific periodicals and the creation of the periodicals development concept. The conditions for the occurrence of positive changes in the publishing process in Universities were determined and named as a new participant in these processes – University library. The list of new tasks inherent in the scientific periodicals of the Universities was presented. The software product «Digital designer» was created as a new applied information technology solution to extend the functionality of the basic system information of the publication according to its editorial policy. Originality. The scientists studied the transformation process of the organizational structure of scientific periodicals publishing in the Universities of Ukraine and the world. It is proved that in today’s conditions for the University publishers of scientific periodicals transition to a new model of publication system of the University scientific periodicals is the most rational, a feature of which is the rejection of purely printing and the introduction of hybrid model of publication. This model assumes that traditional print products is complemented with a form of «Epub ahead of print» (e-publication before printing) using the journal’s website as an operational channel for the dissemination of publications. Practical value. The Universities transition to the new model system for the publication of scientific periodicals, modern concept formation of the scientific journal, creation of relevant software tools (e.g. automation of typesetting the scientific articles and the integration of publications in the database of scientific and technical information) will allow improving the quality of journals and their competitiveness at the international level.